Respirable Crystalline Silica Exposure, Smoking, and Lung Cancer Subtype Risks. A Pooled Analysis of Case–Control Studies - Ge, Calvin; Peters, Susan; Olsson, Ann; Portengen, Lützen; Schüz, Joachim; Almansa, Josué; Behrens, Thomas; Pesch, Beate; Kendzia, Benjamin; Ahrens, Wolfgang; Bencko, Vladimir; Benhamou, Simone; et al. (American journal of respiratory and critical care medicine, 2020)
Millions of workers around the world are exposed to respirable crystalline silica. Although silica is a confirmed human lung carcinogen, little is known regarding the cancer risks associated with low levels of exposure and risks by cancer subtype. However, little is known regarding the disease risks associated with low levels of exposure and risks by cancer subtype. We aimed to address current knowledge gaps in lung cancer risks associated with low levels of occupational silica exposure and the joint effects of smoking and silica exposure on lung cancer risks. Subjects from 14 case-control studies from Europe and Canada with detailed smoking and occupational histories were pooled. A quantitative job-exposure matrix was used to estimate silica exposure by occupation, time period, and geographical region. Logistic regression models were used to estimate exposure-disease associations and the joint effects of silica exposure and smoking on risk of lung cancer. Stratified analyses by smoking history and cancer subtypes were also performed. Our study included 16,901 cases and 20,965 control subjects. Lung cancer odds ratios ranged from 1.15 (95% confidence interval, 1.04-1.27) to 1.45 (95% confidence interval, 1.31-1.60) for groups with the lowest and highest cumulative exposure, respectively. Increasing cumulative silica exposure was associated ( trend < 0.01) with increasing lung cancer risks in nonsilicotics and in current, former, and never-smokers. Increasing exposure was also associated ( trend ≤ 0.01) with increasing risks of lung adenocarcinoma, squamous cell carcinoma, and small cell carcinoma. Supermultiplicative interaction of silica exposure and smoking was observed on overall lung cancer risks; superadditive effects were observed in risks of lung cancer and all three included subtypes. Silica exposure is associated with lung cancer at low exposure levels. An exposure-response relationship was robust and present regardless of smoking, silicosis status, and cancer subtype.